Day 1 IFPRI Presentations for 2023 CGIAR GENDER-ICAR Conference - Ma, Ning; Wallin, Elsa; Bryan, Elizabeth; Davis, Kristin E.; Oingo, Balentine; Ragasa, Catherine; Carrillo, Lucia (2023)
IFPRI is participating in the 2023 annual CGIAR Gender Research Conference. This conference is co-hosted by the CGIAR GENDER Impact Platform and the Indian Council of Agricultural Research (ICAR) and will take place in New Delhi, India, on October 9-12, 2023.